Prevalence of Anemia in Children with Congestive Heart Failure due to Dilated Cardiomyopathy. (19th November 2012) - Mueller, Goetz Christoph; Schlueter, Emmy Lou; Arndt, Florian; Dodge-Khatami, Ali; Weil, Jochen; Mir, Thomas S.
Abstract : Introduction . Anemia is prevalent in adult heart failure patients and appears to be an independent risk factor for morbidity and mortality. The purpose of this work is to determine the prevalence of anemia in children with heart failure from dilated cardiomyopathy (DCM) and to evaluate its influence on morbidity and mortality. Methods . A homogenous group of 58 children with congestive heart failure from DCM was evaluated for heart failure symptoms, appearance of anemia, hospitalization, age of first clinical appearance, necessity of transfusion, and death during medical attendance. Anemic and nonanemic patients were analyzed for differences in age distribution, morbidity, and mortality. Results . Anemia was present in 64% of DCM patients. Hospitalization secondary to heart failure was significantly elevated in heart failure patients with anemia (mean 35.1 ± 40.5 versus 9.97 ± 9.65 days per year, P < 0.05 ). However, mortality was not elevated. Significant relations of age and prevalence of anemia or age and severity of anemia did not appear. Conclusion . Anemia is prevalent in pediatric patients with congestive heart failure from DCM and appears in all age classes. Hospitalization as a surrogate of morbidity is elevated in heart failure patients developing anemia, but mortality risk did not increase.